2012
DOI: 10.1017/s0022215112000485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term, low-dose clarithromycin on T helper 2 cytokines, eosinophilic cationic protein and the ‘regulated on activation, normal T cell expressed and secreted’ chemokine in the nasal secretions of patients with nasal polyposis

Abstract: Clarithromycin has a strong anti-inflammatory effect in nasal polyposis, but has different immunomodulatory effects in allergic and non-allergic nasal polyposis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Additional lower-level evidence supports the use of macrolides, with most using clarithromycin in varying 1032 reported statistically significant reduction in polyp score in both allergic and nonallergic patients and reduction in levels of IL-8 after 8 weeks of treatment with clarithromycin 500 mg daily. Haruna et al 755 suggest that macrolide treatment may be less efficacious in reducing symptoms in patients with predominant eosinophilic disease or severe polyp burden if polypectomy is not initially performed.…”
Section: Viiie3 Crswnp Management: Oral Corticosteroidsmentioning
confidence: 96%
See 1 more Smart Citation
“…Additional lower-level evidence supports the use of macrolides, with most using clarithromycin in varying 1032 reported statistically significant reduction in polyp score in both allergic and nonallergic patients and reduction in levels of IL-8 after 8 weeks of treatment with clarithromycin 500 mg daily. Haruna et al 755 suggest that macrolide treatment may be less efficacious in reducing symptoms in patients with predominant eosinophilic disease or severe polyp burden if polypectomy is not initially performed.…”
Section: Viiie3 Crswnp Management: Oral Corticosteroidsmentioning
confidence: 96%
“…In addition to modulating NF-kB proinflammatory cytokine production, [744][745][746][747][748] studies suggest a non-allergy-mediated role for macrolides in reducing nasal fibroblast proliferation, differentiation, collagen production, and decreased eosinophilic infiltration into nasal epithelium and lamina propria. [1030][1031][1032] An EBRR by Soler et al 752 addressed the utility of macrolide use in CRS. Neither of the 2 RCTs exclusively evaluated CRSwNP patients and just 3 of the remaining 15 retrospective studies specifically assessed CRSwNP patients.…”
Section: Viiie3 Crswnp Management: Oral Corticosteroidsmentioning
confidence: 99%
“…Previous investigations performed by Perić et al (20,21) demonstrated that after eight weeks treatment by 500 mg single oral dose of clarithromycin daily, RANTES and IL-8 levels in nasal secretion samples fell in both allergic and non-allergic patients with nasal polyposis. Eosinophilic cationic protein (ECP) and tumour necrosis factor (TNF)-α levels fell in non-atopic patients, whereas IL-6 and IL-1β concentrations fell in atopic patients with nasal polyps (20,21). So, long-term, low-dose clarithromycin administration has similar anti-inflammatory and variable immunomodulatory effect in these patients.…”
Section: Discussionmentioning
confidence: 92%
“…In vitro roxithromycin administration directly suppresses IL-6 and RANTES production from cultured nasal polyp fibroblasts via the inhibition of IL-6 and RANTES messenger RNA expression (6). Previous investigations performed by Perić et al (20,21) demonstrated that after eight weeks treatment by 500 mg single oral dose of clarithromycin daily, RANTES and IL-8 levels in nasal secretion samples fell in both allergic and non-allergic patients with nasal polyposis. Eosinophilic cationic protein (ECP) and tumour necrosis factor (TNF)-α levels fell in non-atopic patients, whereas IL-6 and IL-1β concentrations fell in atopic patients with nasal polyps (20,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation